Improved solubility, dissolution rate, and oral bioavailability of main biflavonoids from Selaginella doederleinii extract by amorphous solid dispersion - Bing Chen; Xuewen Wang; Yanyan Zhang; Kangping Huang; Hao Liu; Dafen Xu; Shaoguang Li; Qicai Liu; Jianyong Huang; Hong Yao; Xinhua Lin (Taylor & Francis Group, 2020)
Amentoflavone, robustaflavone, 2",3"-dihydro-3',3‴-biapigenin, 3',3‴-binaringenin, and delicaflavone are five major hydrophobic components in the total biflavonoids extract from Selaginella doederleinii (TBESD) that display favorable anticancer properties. The purpose of this study was to develop a new oral delivery formulation to improve the solubilities, dissolution rates, and oral bioavailabilities of the main ingredients in TBESD by the solid dispersion technique. Solid dispersions of TBESD with various hydrophilic polymers were prepared, and different technologies were applied to select the suitable carrier and method. TBESD amorphous solid dispersion (TBESD-ASD) with polyvinylpyrrolidone K-30 was successfully prepared by the solvent evaporation method. The physicochemical properties of TBESD-ASD were investigated by scanning electron microscopy, differential scanning calorimetry, and Fourier-transform infrared spectroscopy. As a result, TBESD was found to be molecularly dispersed in the amorphous carrier. The solubilities and dissolution rates of all five ingredients in the TBESD-ASD were significantly increased (nearly 100% release), compared with raw TBESD. Meanwhile, TBESD-ASD showed good preservation stability for 3 months under accelerated conditions of 40 °C and 75% relative humidity. A subsequent pharmacokinetic study in rats revealed that Cmax and AUC0-t of all five components were significantly increased by the solid dispersion preparation. An in vivo study clearly revealed that compared to raw TBESD, a significant reduction in tumor size and microvascular density occurred after oral administration of TBESD-ASD to xenograft-bearing tumor mice. Collectively, the developed TBESD-ASD with the improved solubility, dissolution rates and oral bio-availabilities of the main ingredients could be a promising chemotherapeutic agent for cancer treatment.